Contemporary surgical management of renal oncocytoma: a nation's outcome. (2nd March 2018) - Neves, Joana B.; Withington, John; Fowler, Sarah; Patki, Prasad; Barod, Ravi; Mumtaz, Faiz; O'Brien, Tim; Aitchison, Michael; Bex, Axel; Tran, Maxine G. B.; ,
Abstract : Objective: To report on the contemporary UK experience of surgical management of renal oncocytomas. Patients and methods: Descriptive analysis of practice and postoperative outcomes of patients with a final histological diagnosis of oncocytoma included in The British Association of Urological Surgeons (BAUS) nephrectomy registry from 01/01/2013 to 31/12/2016. Short‐term outcomes were assessed over a follow‐up of 60 days. Results: Over 4 years, 32 130 renal surgical cases were recorded in the UK, of which 1202 were oncocytomas (3.7%). Most patients were male (756; 62.9%), the median (interquartile range [IQR]) age was 66.8 (13) years. The median (IQR; range) lesion size was 4.1 (3; 1–25) cm, 43.5% were ≤4 cm and 30.3% were 4–7 cm lesions. In all, 35 patients (2.9%) had preoperative renal tumour biopsy. Most patients had minimally invasive surgery, either radical nephrectomy (683 patients; 56.8%), partial nephrectomy (483; 40.2%) or other procedures (36; 3%). One in five patients (243 patients; 20.2%) had in‐hospital complications: 48 were Clavien–Dindo classification grade ≥III (4% of the total cohort), including three deaths. Two additional deaths occurred within 60 days of surgery. The analysis is limited by the study's observational nature, not capturing lesions on surveillance or ablated after biopsy, possible underreporting, short follow‐up, and lack of central histology review. Conclusion: We report on the largest surgical series of renal oncocytomas. In the UK, the complication rate associated with surgical removal of a renal oncocytoma was not negligible. Centralisation of specialist services and increased utilisation of biopsy may inform management, reduce overtreatment, and change patient outcomes for this benign tumour.